Take the Money and Run: Psychopathic Behavior in the Trust Game - Ibáñez, Manuel I.; Sabater-Grande, Gerardo; Barreda-Tarrazona, Iván; Mezquita, Laura; López-Ovejero, Sandra; Villa, Helena; Perakakis, Pandelis; Ortet, Generós; García-Gallego, Aurora; Georgantzís, Nikolaos (Frontiers in Psychology, 2016)
We study the association among different sources of individual differences such as personality, cognitive ability and risk attitudes with trust and reciprocate behavior in an incentivized experimental binary trust game in a sample of 220 (138 females) undergraduate students. The game involves two players, player 1 (P1) and player 2 (P2). In the first stage, P1 decides whether to trust and let P2 decide, or to secure an egalitarian payoff for both players. If P1 trusts P2, the latter can choose between a symmetric payoff that is double than the secure alternative discarded by P1, and an asymmetric payoff in which P2 earns more than in any other case but makes P1 worse off. Before the main experiment, we obtained participants’ scores for Abstract Reasoning (AR), risk attitudes, basic personality characteristics, and specific traits such as psychopathy and impulsivity. During the main experiment, we measured Heart Rate (HR) and Electrodermal Activity (EDA) variation to account for emotional arousal caused by the decision and feedback processes. Our main findings indicate that, on one hand, P1 trust behavior associates to positive emotionality and, specifically, to the extraversion’s warmth facet. In addition, the impulsivity facet of positive urgency also favors trust behavior. No relation to trusting behavior was found for either other major personality aspects or risk attitudes. The physiological results show that participants scoring high in psychopathy exhibit increased EDA and reduced evoked HR deceleration at the moment in which they are asked to decide whether or not to trust. Regarding P2, we find that AR ability and mainly low disagreeable disinhibition favor reciprocal behavior. Specifically, lack of reciprocity significantly relates with a psychopathic, highly disinhibited and impulsive personality. Thus, the present study suggests that personality characteristics would play a significant role in different behaviors underlying cooperation, with extraversion/positive emotionality being more relevant for initiating cooperation, and low disagreeable disinhibition for maintaining it.